How entrepreneurial leaders use emotional labour to improve employee attitudes and firm performance. (2018) - Batchelor, John H.; Humphrey, Ronald H.; Burch, Gerald F.
This study takes a deep look at how entrepreneurial leaders use all three forms of emotional labour. The results from this analysis of 147 dyadic pairs of entrepreneurial leaders and their subordinates are presented herein. This study is the first to investigate the relationship between emotional labour strategy and the display of discrete genuine emotions (enthusiasm, liking, irritation). Leader genuine emotional labour and leader displays of positive discrete emotions were positively correlated with employee job satisfaction, affective commitment, and lower intentions to quit. Additionally, this study provides empirical evidence that the display of discrete emotions moderates the effects of leader genuine emotion on firm performance. From a practical standpoint this study benefits entrepreneurs by outlining emotionally healthy methods to display the appropriate emotions when interacting with stakeholders to enhance firm performance.